Critical Review of Murābaḥah Financing in Contemporary Islamic Banking: A Maqāṣid al-Sharī‘ah Perspective - Djumadi; Arzal Syah; Hamida; Mujahidin; Kamiruddin (MILRev: Metro Islamic Law Review, 2025)
This study critically analyses the implementation of murābaḥah contracts in contemporary Islamic banking through the lens of maqāṣid al-sharī‘ah theory. Murābaḥah has long been recognised as one of the dominant financing schemes in Sharia banks, particularly in Indonesia, where it plays a central role in meeting customer needs ranging from consumption to investment. However, in today's context of rapid financial innovation and global competition, questions remain regarding its alignment with the broader objectives of Islamic law beyond mere technical compliance. The research employs a descriptive qualitative approach, utilising in-depth interviews, direct observations, and documentation studies. The primary object of inquiry is Sharia banks in Indonesia, with informants drawn from banking practitioners and customers. This dual perspective provides a more comprehensive understanding of how murābaḥah is designed, implemented, and perceived in practice within the dynamics of modern Islamic banking. The findings indicate that although murābaḥah contracts are generally implemented in line with formal sharia procedures, the embodiment of maqāṣid al-sharī‘ah values remains partial. Elements such as justice, fair profit, social welfare, and mutual assistance are evident but fragmented and lack institutional standardisation. As a result, the spirit of maqāṣid al-sharī‘ah is not yet fully realised in contemporary practice. This study concludes that there is an urgent need to reformulate the strategy and design of murābaḥah products to reflect the holistic objectives of maqāṣid al-sharī‘ah better better. This involves preserving wealth and prohibiting usury and safeguarding life, intellect, and lineage. The research contributes by exposing the gap between formal compliance and substantive realisation, offering novelty in reframing murābaḥah as a contemporary instrument for promoting justice, welfare, and sustainable Islamic finance.